If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -2x + -7 + -2 = 4x + 7 Reorder the terms: 16 + -7 + -2 + -2x = 4x + 7 Combine like terms: 16 + -7 = 9 9 + -2 + -2x = 4x + 7 Combine like terms: 9 + -2 = 7 7 + -2x = 4x + 7 Reorder the terms: 7 + -2x = 7 + 4x Add '-7' to each side of the equation. 7 + -7 + -2x = 7 + -7 + 4x Combine like terms: 7 + -7 = 0 0 + -2x = 7 + -7 + 4x -2x = 7 + -7 + 4x Combine like terms: 7 + -7 = 0 -2x = 0 + 4x -2x = 4x Solving -2x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2x + -4x = 4x + -4x Combine like terms: -2x + -4x = -6x -6x = 4x + -4x Combine like terms: 4x + -4x = 0 -6x = 0 Divide each side by '-6'. x = 0 Simplifying x = 0
| -14r=49 | | 27-5x=-7 | | 11x^2-31x-10=0 | | 5(I-4)=4-3k | | 3+6=9+32 | | 7x^2+84=0 | | 3+x=9+32 | | x+2x=165 | | 42=-7(j-4) | | -10x-7=-5x-3 | | Y-21=-12 | | 7x-9=6x-2 | | 4x-11(2x-3)+15(x+7)= | | 2x^2-42x=-40 | | 6x+10=14+2x | | 8-6s=-40 | | -12+3r=-57 | | x+2x+14=80 | | -9x-3=-30 | | -8t-3=29 | | 3x-5(-4+2x)=2 | | 2m-9=15 | | 3(n+2)=30+n | | 32=8(p+3) | | 4(w-9)=7w+18 | | 12x+19=3x+163 | | x(2x^4-5x^2+4)= | | 4r+41+5r=104 | | 70-6x=3x+22 | | 13-8x=198-43x | | 3(3+n)=19+n | | 8+2(x-5)=14 |